IMPLEMENTASI PELAYANAN E-KTP DI KANTOR CAMAT SANGA SANGA KABUPETEN KUTAI KARTANEGARA - Abdul Rivai (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the E-ID Card Implementation Services at the District Office Sangasanga Kutai regency. The object of the research findings demonstrate implementation of e-ID card service in the district of Kutai regency Sangasanga have implemented the appropriate mechanism, but in the service delivery process of the e-ID card is still confronted by many obstacles so the e-ID card service cumulatively less than optimal. It can be known from the sub-set of research focus that is not everything can be run effectively. Lack of effective implementation of e-ID card service in the District Sangasanga can be known from the aspect of human resources (personnel carrier) and inadequate computer facilities, so that the applicative, both in the process of administration, as well as data recording less effective.